Variations in leaf phyllosphere microbial communities and development of tobacco brown spot before and after fungicide application - Xiang, Li-Gang; Wang, Han-Cheng; Cai, Liu-Ti; Guo, Tao; Luo, Fei; Hsiang, Tom; Yu, Zhi-He (Frontiers in Microbiology, 2022)
In recent years, STROBY (50% Kresoxim-methyl) has been widely used to control tobacco brown spot in Guizhou province, China. As a broad-spectrum fungicide, STROBY targets not only phytopathogens, but affects many other microorganisms including those pathogenic, beneficial, or neutral to the plant hosts. To understand the effects of STROBY on the phyllosphere microbial communities of tobacco leaves during the development of tobacco brown spot, the fungal and bacterial communities of symptomatic and asymptomatic leaves at four time points, before spraying (Aug29) and after spraying (Sep3, Sep8, Sep13), were investigated using the Illumina high-throughput sequencing. The results showed that STROBY had significant effects on the phyllosphere microbial communities of tobacco leaves. Microbial communities in asymptomatic leaves were more greatly affected than their counterparts in symptomatic leaves, and fungal communities were more sensitive than bacterial communities. Throughout the experiment, the most common genera in symptomatic leaves were Alternaria, Pseudomonas, Pantoea, and Sphingomonas, and in asymptomatic leaves, these were Golubevia and Pantoea. After spraying, the alpha diversity of fungal communities increased in symptomatic leaves and decreased in asymptomatic leaves, while the alpha diversity of bacteria increased in both types of leaves. Beta diversity showed that in asymptomatic leaves, the fungal communities in the first stage was significantly different from the remaining three stages. In contrast, the fungal communities in symptomatic leaves and the bacterial communities in all leaves did not fluctuate significantly during the four stages. Before spraying (Aug29), the dominant functions of the fungal community were animal pathogen, endophyte, plant pathogen, and wood saprotroph. Whereas after spraying (Sep3, Sep8, Sep13), the proportion of the above fungal functions decreased and the unassigned functions increased, especially in asymptomatic leaves. This study describes the effects of STROBY application and tobacco brown spot presence in shaping the leaf phyllosphere microbial communities, and provides insights into the microbial community effects on tobacco leaves of a strobilurin fungicide.